2003
DOI: 10.1002/chem.200204635
|View full text |Cite
|
Sign up to set email alerts
|

Formation of MoS2 Inorganic Fullerenes (IFs) by the Reaction of MoO3 Nanobelts and S

Abstract: The reaction of MoO3 and S at temperatures higher than 300 degrees C in an argon atmosphere provides a convenient and effective method for the synthesis of MoS2 nanocrystalline substances. MoS2 nanotubes and fullerene-like nanoparticles have been obtained by the reaction at 850 degrees C under well-controlled conditions. The influences of reaction temperature and duration were carefully investigated in this paper. All of the nanostructures were characterized by Xray powder diffraction (XRD), transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
152
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(158 citation statements)
references
References 62 publications
3
152
1
2
Order By: Relevance
“…Electron hopping among grains would significantly decrease the mobilities in MoS 2 . 22,23 In addition, other defects including cationic vacancies, dislocation and adsorption-induced doping effect in the MoS 2 are also possible reasons for the low mobilities, which are always observed in CVD-prepared two dimensional materials like graphene. 14 The mobility could be significantly improved by annealing the as-prepared samples, 8,20 using local top-gate with high-κ dielectric, 8,21 and optimizing the growth conditions.…”
mentioning
confidence: 99%
“…Electron hopping among grains would significantly decrease the mobilities in MoS 2 . 22,23 In addition, other defects including cationic vacancies, dislocation and adsorption-induced doping effect in the MoS 2 are also possible reasons for the low mobilities, which are always observed in CVD-prepared two dimensional materials like graphene. 14 The mobility could be significantly improved by annealing the as-prepared samples, 8,20 using local top-gate with high-κ dielectric, 8,21 and optimizing the growth conditions.…”
mentioning
confidence: 99%
“…After the temperature was kept at 850 °C for 10 min, at such a high temperature, MoO 3 powder evaporated and reacts with sulfur vapor to form volatile suboxide MoO 3-x . [13] these suboxide compounds diffused to the substrate and further reacted with sulfur vapor to grow MoS 2 films [15] . Finally, the furnace was cooled down to room temperature naturally.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that MoS 2 formed as the result of the stepwise reaction of substitution and reduction which lead to an intermediate product of MoO 3-x . [13,16] Although the growth dynamics of MoO 3-x and sulfur are still not fully understood, there are two possible channels for the surface growth that can be expected: (1) MoO 3-x species adsorb and diffuse on the substrate, reacting with S to form MoS 2 ; (2) MoO 3-x and sulfur react directly in the gas phase, and the resulting MoS 2 clusters adsorb, nucleate, and grow on the substrate [17] . In our experiment, the reaction process is described as follows.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations